Lower cretaceous terrestrial palynomorph biostratigraphy of the McMurray Formation, northeastern Alberta ... - Burden, Elliott T. (University of Calgary, 1982)
Bibliography: p. 118-149. ... : Abundant and diverse palynomorphs from the McMurray Formation of northeastern Alberta are examined and correlated with palynomorphs of the Ellerslie Member in central Alberta and Sunburst and Calcareous members of the lower part of the Kootenai Formation, near Great Falls, Montana. Three terrestrial palynomorph assemblage-zones and one Oppel-zone are recognized. In ascending order, the is overlain by the Impardecispora trioreticulosus-Fora~inisporis asymmetricus Oppel-zone , the Retimonocolpites crassatus-Kuylisporites lunaris Assemblage-zone and the Retimonocolp~tes peroreticulatus-Liliacidites inaegualis Assemblage-zone. Lower McNurray strata correlate biostratigraphically with Ellerslie and Sunburst strata of Alberta and Montana; Valanginian to early Barremian ages are inferred from palynology. Middle McMurray strata correlate with uppermost Ellerslie and Sunburst members, Calcareous member and an unnamed lignitic unit; Barremian through early Aptian ages are indicated. Upper McMurray strata of probable ...